Utilization Of Songket Fabric As A Wedding Dress With The Application Of Aesthetic Principles - Arina Haq; Anita Shofiyunada (An International Journal Tourism and Community Review, 2024)
Songket fabric is one of the traditional fabrics originating from South Sumatra, songket fabric has been used as a subordinate of traditional clothing, it can be in the form of bodo clothes, tunics. The development of fashion that continues to rotate so that the preservation of this songket fabric is maintained, innovation is needed, to provide innovation so that songket fabric can be processed into fashion for wedding occasions with more modern models. The principle of aesthetics is a reference in creating innovations so that the results of innovation are in accordance with the intentions and goals. The problem is how to use songket fabric as a wedding dress by applying aesthetic principles. The purpose is to find out the use of songket fabric as a wedding dress by applying aesthetic principles. The data collection methods used are observation, documentation and literature. The data analysis used is qualitative data analysis. The manufacture of wedding dress using songket fabric and a combination of tulle fabric through the process of determining design, preparing tools and materials, taking measurements, making patterns, cutting materials, marking the patterns, sewing, pressing, and finishing. Unity lies in detail by detail is still continuous, balance lies in symmetrical balance and contrast is applied to the selection of materials in terms of texture and color. Wedding Dress clothing is as follows; using songket fabrics. The use of this songket fabric is a synthetic songket fabric, which is widely sold and the price is still affordable. There are different possibilities when using the original songket.